2022
DOI: 10.3389/fenvs.2022.1094404
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the height of the pollution boundary layer and their meteorological effects on the distribution of surface ozone concentrations

Abstract: Focusing on the key air pollution regions in China by using hourly automatic weather data, ground-based and high-altitude meteorological sounding data, and near-surface O3 monitoring data, here, we try to quantify the relationship between boundary layer meteorological condition and near-surface O3 concentrations. The key meteorological element includes changes in solar zenith angle, cloud height, atmospheric condensation rate, and the associated change in the boundary layer height. We also try to better unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The main process is the oxidation of NO by atmospheric oxidants to produce NO 2 and the photolysis of NO 2 to produce O 3 . Temperature and solar radiation play important roles in the formation and transport of O 3 [12].…”
Section: O3 Pollution Daily Variation Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main process is the oxidation of NO by atmospheric oxidants to produce NO 2 and the photolysis of NO 2 to produce O 3 . Temperature and solar radiation play important roles in the formation and transport of O 3 [12].…”
Section: O3 Pollution Daily Variation Characteristicsmentioning
confidence: 99%
“…Previous studies have shown that surface O 3 concentrations in many cities in the central and southern regions have been increasing year by year [10,11], and it is important to strengthen regional O 3 pollution control. In addition to the levels influenced by precursors, meteorological factors and weather systems also play an important role in the formation, dilution, and transport of O 3 [12,13]. Weather with strong solar radiation, high atmospheric temperature, and low relative humidity are key meteorological factors that promote the formation of O 3 photochemical reactions [14].…”
Section: Introductionmentioning
confidence: 99%